The Mechanism of Interregional Redistributions of Money - Gilbert, J. C. (Review of Economic Studies, 1938)
Journal Article The Mechanism of Interregional Redistributions of Money Get access J. C. Gilbert J. C. Gilbert Dundee Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 3, June 1938, Pages 187–194, https://doi.org/10.2307/2967446 Published: 01 June 1938